Synthesis and crystal structures of copper, nickel and zinc complexes derived from 2-((2-(pyrrolidin-1-yl)ethylimino)methyl)phenol with antimicrobial activity. (1st February 2023) - Tan, Yao; Lei, Yan
Graphical abstract: Five new copper(II), nickel(II) and zinc(II) complexes derived from 2-((2-(pyrrolidin-1-yl)ethylimino)methyl)phenol were synthesized and structurally characterized. Single crystal X-ray analysis indicates that the Cu atoms in the tetranuclear complexes 1 and 2 are in a square pyramidal coordination, the Ni atoms in the trinuclear complexes 3 and 4 are in an octahedral coordination and the Zn atom in the mononuclear complex 5 is in a tetrahedral coordination. In vitro bacterial viability revealed that the copper and zinc complexes have effective antimicrobial activity against B. subtilis, S. aureus, E. coli and P. fluorescens, and general activity against the fungal strains C. albicans and A. niger . Abstract: Five new copper(II), nickel(II) and zinc(II) complexes, [Cu4 Cl2 (μ1, 1 -N3 )4 (DMF)2 ] (1 ), [Cu4 Br2 (μ1, 1 -N3 )4 (DMF)2 ] (2 ), [Ni3 L2 (CH3 COO)4 ]CH3 OH (3 ), [Ni3 L2 (CH3 COO)2 (μ1, 1 -N3 )2 (CH3 OH)2 ] (4 ) and [Zn(LH)I2 ]CH3 OH (5 ), were designed and successfully synthesized using the Schiff base ligand 2-((2-(pyrrolidin-1-yl)ethylimino)methyl)phenol (HL). All the synthesized complexes were characterized using different physico-chemical and spectroscopic methods, like elemental analysis, infrared spectra and single crystal X-ray diffraction. The X-ray structural analysis showed that the Cu atoms in the tetranuclear complexes 1 and 2 are in a square pyramidal coordination, the Ni atoms in the trinuclear complexes 3 and 4 are in an octahedral coordination and the Zn atom in the mononuclear complex 5 is in a tetrahedral coordination. The Schiff base ligand was coordinated to the metal atoms through the phenolate oxygen, imino nitrogen and/or pyrrolidine nitrogen atoms. The biological study indicated that the copper and zinc complexes have interesting antimicrobial activity against B. subtilis, S. aureus, E. coli and P. fluorescens, with MIC values of 0.6–2.3 μmol/L.